Tablets Vs. Smart Phones: The Battle of the Century - Santandreu, Juan; Shurden, Michael C. (Journal of Marketing Development and Competitiveness, 2017)
Technological advances are at the forefront of the innovation revolution that we are experiencing today. As smart phones and tablets have improved and evolved, they have complemented each other but mostly, time after time, they are duplicating many of their functions. This duplication could lead to a potential merge or synergistic effect resulting in one product that offers the best of both worlds. The authors are exploring the levels of preference for different applications that are available in both smart phones and tablets. These applications include schoolwork, access to software, general organizer, communications and social medial, and personal use.